Dialog über Deutschland : Studien zur Deutschlandpolitik von KPdSU und SED (1960 - 1979) - Schmidt, Karl-Heinz 1936- (Nomos-Verl.-Ges, 1998)
Studien zur Deutschlandpolitik von KPdSU und SED (1960-1979)